PRELIMINARY STUDY OF LARVAL DEVELOPMENT Oryzias javanicus IN INDONESIA - Rachma Puspitasari; . Suratno (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
Java medaka Oryzias javanicus potentially developed as test organism, represents the coastal region because it has a high adaptability in freshwater, brackishwater and marine environments. Utilization of it as a test organism has some obstacles such as lack of number of test organisms with same size or age. The fulfillment of number can be solved if the test organism is cultivated exclusively in the laboratory. This study was a preliminary study to get information about suitable salinity for spawning and hatching. Parameter observed were spawning ability in 0 and 20 ppt and hatching rate of egg among 0. 15 and 30 ppt and development of larval fish in 0 ppt. Result indicated that the fish was be able to spawn in 0 and 20 ppt. Eggs were hatched within 9 days in 30 ppt, faster than in freshwater and 15 ppt. In general, O. javanicus was be able to spawn either in freshwater or seawater, but there are differences in the behavior of fish in the laying of egg. Fish will carried their eggs in the abdomen in freshwater, while 20 ppt salinity fish tends to release the eggs. O. javanicus be able to live and lay eggs on freshwater and seawater. Selection of salinity is adjusted to test requirement in egg phase, pascalarva or adult. In general, breeding of fish easier and faster done in fresh water while hatching eggs take place more quickly in high salinity.Keywords: Indonesia, Java Medaka, Oryzias javanicus, test organism